Performance of Adult Pyeloplasty Relative to Endourological Management in the Era of Robotic Surgery: Data from the Nationwide Inpatient Sample. Issue 2 (March 2018) - Colaco, Marc; Caveney, Maxx K.; Terlecki, Ryan P.
Abstract : Introduction: : Reports of robot‐assisted pyeloplasty have increased. However, it is unclear if this change is due to increased diagnosis of adult ureteropelvic junction obstruction, a shift in management based on presumed efficacy, a desire to maximize robot use or some combination thereof. Therefore, we acquired and analyzed data on a national scale to determine the incidence of interventions to correct ureteropelvic junction obstruction in adults and to characterize trends in procedure selection. Methods: : Patients older than 18 years with ICD‐9 procedure codes 55.87 (pyeloplasty) and 55.11 (endopyelotomy) were included in the study, with attention to those designated laparoscopic robotic assistance (17.42). Data were collected for the period from January 2000 through December 2012, and weighted to a national average using Nationwide Inpatient Sample guidelines. Results: : A total of 47, 992 pyeloplasties were identified. Pyeloplasty rates exhibited a significant increase during this period [F(1, 11)=41.38, p <0.01] and endopyelotomy rates exhibited a significant decrease [F(1, 11)=64.7, p <0.01]. A higher percentage of pyeloplasties were performed robotically in 2012 vs 2009 (54% vs 44%, p <0.010). Conclusions: : Rates of pyeloplasty appear to be increasing at the expense of endopyelotomy. The percentage of pyeloplasty cases performed robotically is increasing but it is unclear if this is due to superior results or a need for increased robot use.